Vliv simulace 4D na BIM modely infrastrukturních staveb - Boháč, Milan (Vysoké učení technické v Brně. Fakulta stavební, 2025)
Diplomová práce se zaměřuje na vliv simulace 4D na BIM modely infrastrukturních staveb, kde podkladem byl projekt dálnice D35 Opatovec - Staré Město ve stupni DSP. Cílem diplomové práce je poukázat na možnosti tvorby simulace 4D, její využití a vliv na samotnou tvorbu BIM modelu infrastrukturních staveb. Práce se zaobírá nad kvalitou vstupních modelů, účelu využití a i nad samotnou tvorbou v programu Autodesk Navisworks Manage.

The diploma thesis focuses on the influence of 4D simulation on BIM models of infrastructure structures, where the project D35 Opatovec - Staré Město motorway in the DSP stage was the basis. The goal of the thesis is to highlight the possibilities of creating 4D simulation, its use and its influence on the actual creation of BIM model of infrastructure structures. The thesis deals with the quality of the input models, the purpose of use and the actual creation in Autodesk Navisworks Manage.
The Influence of 4D Simulation on BIM Models of Infrastructure Buildings
Keywords: 4D simulace; BIM; D35; DSP; PPP; Autodesk Navisworks Manage; Harmonogram; RoadPAC; Autodesk Civil 3D; Autodesk Revit; vizuální kontrola; modely; 4D simulation; BIM; D35; DSP; PPP; Autodesk Navisworks Manage; Schedule; RoadPAC; Autodesk Civil 3D; Autodesk Revit; visual inspection; models